Decoding Data Use: How do leaders source data and use it to accelerate development? - Masaki, Takaaki; Custer, Samantha; Eskenazi, Agustina; Stern, Elena; Latourell, Rebecca (AidData at William & Mary, 2017)
Nov 28, 2017 |

6 key insights into the data and information education leaders want most - Custer, Samantha; King, Elizabeth; Atinc, Tamar; Read, Lindsay; Sethi, Tanya (2018)

Toward Data-Driven Education Systems: Insights into using information to measure results and manage change - Custer, Samantha; King, Elizabeth; Atinc, Tamar Manuelyan; Read, Lindsay; Sethi, Tanya (Brookings Institute, 2018)
Keywords: ⛔ No DOI found

6 key insights into the data and information education leaders want most - Custer, Samantha; King, Elizabeth; Atinc, Tamar Manuelyan; Read, Lindsay; Sethi, Tanya (Brookings Institute, 2018)
Researchers summarize their new analysis of two unique global surveys that assess the use of data and evidence by education leaders in developing countries.